Effects of General Anaesthesia on the Middle Ear Pressure - Deniz, Engin (Turk J Anaesthesiol Reanim, 2019)
OBJECTIVE: Inhalation agents can have different effects on the middle ear pressure (MEP). We aimed to investigate the effect of sevoflurane and desflurane, the agents used in patients who do not have any ear pathology and who undergo surgery under general anaesthesia, on MEP. METHODS: Fifty adult patients who were scheduled to undergo inguinal hernia and lower extremity surgery were included in our study. All patients were aged between 20 and 60 years and belonged to the American Society of Anesthesiologists (ASA) I–III class. Patients were divided into two groups, according to the inhalation agent administered for the surgery: sevofluran, Group S (n=25); and desfluran, Group D (n=25). Anaesthetic agents, intraoperative end tidal carbon dioxide and airway pressures were recorded. The MEP was measured for both ears preoperatively, at the intraoperative 5(th), 10(th), 15(th) minutes, and at the postoperative 10(th) and 30(th) minutes. RESULTS: The MEP at the intraoperative 10(th) minute was significantly higher in Group D compared to Group S. In Group D, the MEP increased significantly at the intraoperative 10(th) and 15(th) minutes, and postoperative 30th minute, compared to preoperative values. In Group S, the MEP increased significantly at the postoperative 10(th) minute, compared to preoperative values. CONCLUSION: We found that desflurane increases the MEP during the intraoperative and postoperative period, compared to sevoflurane.